A Case of Giant Cutaneous Lopez Type III Meningioma of the Scalp - Cheng, Man Fung; Cheung, Ling Kit; Dodoo, Ernest Addy; Po, Yin Chung (Journal of Neurological Surgery Reports, 2023)
Meningiomas are the most common central nervous system (CNS) tumors. Extracranial meningiomas are rare, constituting 2% of all meningiomas. We describe a case of Lopez type III meningioma of the scalp in a 72-year-old gentleman who had a long-standing giant scalp mass and presented with recent mild left-sided limb weakness and numbness. Magnetic resonance imaging (MRI) of the skull demonstrated a right frontoparietal tumor extending through the skull into the scalp. Tumor excision revealed World Health Organization (WHO) grade 1 meningioma. Clinicians should correlate a cutaneous skull mass and new onset of neurological symptoms. Cutaneous meningioma is an important differential diagnosis.
Keywords: scalp mass; cutaneous meningioma; Lopez classification; extracranial extension